Program of work in health in the inland – pits: a strategy that has worked out - Ana Débora Assis Moura; Guldemar Gomes de Lima; Adna Ribeiro Braquehais (Rev Rene)
Study of quantitative nature, developed with the objective of gathering a sample of the indicators of health in Alto Santo before the implementation of PITS, in the years of 1999 and 2000, and after the implementation, in the years of 2002 and 2003. The data collection was accomplished through SIAB, in the Municipal Bureau of Health, in April of 2004. The sample consisted of the information consolidated in the years of 1999, 2000, 2002 and 2003. The data were grouped in 07 charts, and analyzed according to the technique of content analysis. A decrease in the infant mortality was verified; attendance to children, focusing on breastfeeding, immunization, control of malnutrition and diseases prevalent in childhood; attendance to 99% of the pregnant women; reduction of hospitalizations; attendance to the largest number of families by the health team. We concluded that PITS came to improve the situation of health in the municipal district considerably, emphasizing mainly the prevention and promotion of health attributed as a nurse’s role.